PHOSPHORITES OF THE OGASAWARA PLATEAU, NORTHWESTERN PACIFIC - Volokhin Y.G.; Vasil'yev B.I.; Govorov I.N. (My University, 1988)
Large high-grade phosphorite bodies were found on the Ogasawara Plateau near the junction of the Izu and the Volcano Trenches, on the 4th cruise of the R/V Akademik A. Nesmeyanov between July and September 1984, as well as on the 7th cruise of the R/V Akademik A. Vinogradov between January and April 1986. Dredging and coring of unconsolidated material, continuous seismoacoustic profiling and biostratigraphic, petrographic and geochemical investigations revealed the extent of these phosphorite bodies, as well as their genesis, and allowed the phosphate ore reserves to be estimated. Areas of high-grade ore on the Ogasawara Plateau are outlined by the 2000-m depth contour, i.e., the base of reef limestones on the central and eastern massifs. The P2O5 content of phosphorite here reaches 25 to 31 percent.